Factors Affecting Job Performance: A Review of Literature - Jankingthong, Korkaew; Rurkkhum, Suthinee (Humanities, Arts and Social Sciences Studies, 2013)
The purpose of this study is to investigate existing literature and theory in order to initially construct a conceptual framework of SEM factors affecting job performance. The results of the study revealed that organizational justice, work engagement, and public service motivation(PSM) have direct effects toward job performance. Transformational leadership, however, has both direct and indirect effects toward job performance.